Engineering chemically modified viruses for prostate cancer cell recognition. Issue 12 (14th October 2015) - Mohan, K.; Weiss, G. A.
Abstract : Viruses wrapped with peptide ligand-functionalized PEG allowed differentiation of biomarker levels on prostate cancer cells distinguishing disease aggressiveness. Abstract : Specific detection of circulating tumor cells and characterization of their aggressiveness could improve cancer diagnostics and treatment. Metastasis results from such tumor cells, and causes the majority of cancer deaths. Chemically modified viruses could provide an inexpensive and efficient approach to detect tumor cells and quantitate their cell surface biomarkers. However, non-specific adhesion between the cell surface receptors and the virus surface presents a challenge. This report describes wrapping the virus surface with different PEG architectures, including as fusions to oligolysine, linkers, spacers and scaffolded ligands. The reported PEG wrappers can reduce by >75% the non-specific adhesion of phage to cell surfaces. Dynamic light scattering verified the non-covalent attachment by the reported wrappers as increased sizes of the virus particles. Further modifications resulted in specific detection of prostate cancer cells expressing PSMA, a key prostate cancer biomarker. The approach allowed quantification of PSMA levels on the cell surface, and could distinguish more aggressive forms of the disease.